Public Response to the Government's COVID 19 Mitigation Policy: 2020 National Online Qualitative Survey - Ari Darmastuti; Arizka Warganegara; Khairunisa Maulida (Universitas Sultan Ageng Tirtayasa, 2020)
The success of the COVID19 mitigation policy depends on many things, the most important of which is the performance of the government and the trust between fellow citizens in one state entity. This study aims to see people's perceptions of the government's response to the handling of COVID 19. The method used is an online qualitative survey. This national online qualitative survey represents respondents from 6 (six) major islands in Indonesia, namely Sumatra, Java, Kalimantan, Sulawesi, Bali and Papua. The results of this research survey are First, 53.4% of respondents expressed dissatisfaction with the government's performance in handling the COVID 19 Pandemic. Second, 50.2% of respondents stated that Anies Baswedan was the governor whose most responsive governor was the COVID 19 Pandemic. Third, 51.1% of respondents stated that the DKI Jakarta Regional Government is considered to be the most responsive local government to COVID 19. Fourth, 46.7% of respondents chose the provision of massive rapid test kits at Puskesmas as the main thing that must be done by the government for better handling of COVID 19. Fifth, 55.9% of respondents stated that the National Government vis a vis BNPN-the Task Force for the Acceleration of Handling Corona Virus (COVID 19) as the most authorized institution in handling COVID 19.